1967
DOI: 10.1172/jci105648
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Parathyroid Responsiveness in Vitamin D—Deficient Rats by Parenteral Calcium or Dietary Lactose*

Abstract: Abstract. The effects of treatment with vitamin D, calcium, or lactose on the responsiveness of vitamin D-deficient rats to parathyroid hormone were compared. In the absence of vitamin D, parenteral calcium or dietary lactose administration resulted in increases in serum calcium concentration although not to the normal values obtained in animals given vitamin D. Dietary lactose also partially restored the low bone calcium content of vitamin D-deficient rats. Untreated vitamin D-deficient rats showed no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

1969
1969
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…Unlike the vitamin D-deficient animal, however, the serum calciums of the PTX-calcium supplemented animals, although lower than normal, were never at the hypocalcemic levels which have been shown to decrease bone maturation (33). Rather, the 8.3 mg/100 ml serum calcium, which was maintained in this study (Table I), was comparable to the serum calcium concentration which Au and Raisz (34) found sufficient to maintain skeletal responsiveness in PTX rats. Thus the 250HD3 effect on bone in the present study cannot be solely a secondary reflection of the reversed hypocalcemia.…”
Section: Discussioncontrasting
confidence: 39%
“…Unlike the vitamin D-deficient animal, however, the serum calciums of the PTX-calcium supplemented animals, although lower than normal, were never at the hypocalcemic levels which have been shown to decrease bone maturation (33). Rather, the 8.3 mg/100 ml serum calcium, which was maintained in this study (Table I), was comparable to the serum calcium concentration which Au and Raisz (34) found sufficient to maintain skeletal responsiveness in PTX rats. Thus the 250HD3 effect on bone in the present study cannot be solely a secondary reflection of the reversed hypocalcemia.…”
Section: Discussioncontrasting
confidence: 39%
“…Au and Raisz (12) found that parenteral calcium did restore the response to parathyroid extract in rats. In puppies, complete restoration of the response was not achieved in rachitic animals despite a rise to near normal values for the serum calcium.…”
Section: Discussionmentioning
confidence: 97%
“…Vitamin D-deficient diets supplemented with high calcium and lactose have been used previously to maintain normocalcemia in vitamin D-deficient rats (15,16). In all cases, protein was given in the form of casein, and the amount of inorganic sulfate in the diets was similar.…”
Section: Camentioning
confidence: 99%
“…Alternatively, increased intestinal absorption of sulfate could occur in this group of rats by a mechanism independent of Na-SO 4 cotransport activity. In this regard, a lactose-induced enhancement of the passive (or diffusional) component of calcium transport has been suggested to explain the ability of lactose to increase intestinal calcium absorption (15,16). An analogous mechanism might be responsible for increasing intestinal sulfate uptake, thereby increasing serum sulfate concentrations.…”
mentioning
confidence: 99%